Physicochemical properties and sensory evaluation of dried vegetable meatballs from soy protein isolates - Domas Galih Patria; Sukamto Sukamto; Sutrisno Adi Prayitno; Nadhifah Salsabila; Jenshinn Lin (AGROINTEK, 2024)
Meatballs are a popular food in Indonesia. Vegetable meatballs (VM) are not as popular as meatballs. The utilization of soy protein isolate (SPI) in vegetable meatballs is expected to improve the functional quality of the meatballs. SPI is useful as a source of essential amino acids the body needs. SPI acts as a binder and gelling agent during processing and improves emulsion stability. This study aims to investigate the use of soy protein isolate in making vegetable meatballs (VM) and its effect on sensory and characteristic properties. The treatment material in this study was the use of SPI in meatball dough as a substitute for meat. The study used a completely randomized design (CRD) consisting of five treatments, namely the ratio of tapioca flour and SPI with treatments (VM0) 100:0%, (VM1) 80:20%, (VM2) 70:30%, (VM3) 60:40% and (VM4) 50:50% and analyzed triplicate. The investigated parameters of this investigation were: volume, weight, bulk density, cooking yield, water retention, proximate, and sensory evaluation. The results showed that using SPI 30% by weight of starch gave the best results. The value of the volume expansion ratio is 1.52 ml/ml, water reabsorption is 308.20%, bulk density is 0.64 g/ml, cooking yield is 218.84 %, and moisture retention is 227.54%. Crude protein content 29.417%. The preference score of vegetable meatballs is quite good, which is between 4 to 4.5 for color, aroma, and elasticity, while for taste and aroma, it is an average of 3.5. Although it is still lower than meatballs, vegetable meatballs provide a choice of healthy meatballs. It is expected that the results of this study will be able to produce VM that contains high vegetable protein and lower prices.